IAEA Safety Guides vs. Actual Challenges for Design and Conduct of Indoor Radon Surveys - Andrey Tsapalov; Konstantin Kovler; Sergey Kiselev; Ilia Yarmoshenko; Robert Bobkier; Petr Miklyaev (Atmosphere)
An analysis of the international radon regulatory framework identified actual challenges for the design and conduct of indoor radon surveys, though there is little discussion on this issue in the radon community. The main challenges hindering the development of radon regulation on an international scale, particularly in indoor radon surveys include the following: (i) responsibility for indoor radon testing and mitigation, (ii) excessive focus on Radon Priority Areas, (iii) the role of temporal uncertainty in indoor radon testing, (iv) the standardization of indoor radon measurements, and (v) the standardization of thoron EEC measurements and indoor testing. To address these gaps and inconsistencies, actual needs for design and conduct of indoor radon surveys are proposed, covering the aforementioned challenges. The needs statement, including a discussion of solutions, addresses the following key aspects of radon regulation: (1) legislation, (2) radon measurements, (3) awareness, and (4) building protection. The focus remains on the radon measurement aspect, detailing the strategy and tools for conducting indoor radon surveys within a rational approach. This includes the main research activities necessary for the sustainable development of global radon regulation. The final part of the article presents a Rational Method (protocol) of indoor radon measurements serving as a detailed guideline for standardizing indoor radon testing at the international level. This ensures the decision-making reliability of at least 95% and harmonizes relevant national approaches considering traditional measurement protocols using both short-term and long-term measurements. The proposed solutions aim to achieve the goal of a modern design and conduct of indoor radon surveys that are consistent with large-scale (mass) testing and effectively identify hazardous buildings. These solutions are based on a rational approach with convenient tools and active voluntary participation of the population to be implemented within the framework of national radon regulation.